Question Number 101522 by bramlex last updated on 03/Jul/20

calculate : cos ^2 47^o +cos ^2 73^o +cos 47^o .cos 73^o +(1/2)

Commented bybemath last updated on 03/Jul/20

= (cos 47^o +cos 73^o )^2 −cos 73^o .cos 43^o +(1/2)  = (2cos 60^o .cos 13^o )^2 −(1/2)(cos 120^o +cos 26^o )+(1/2)  = cos ^2 13^o +(1/4)−(1/2)cos 26^o +(1/2)  =(3/4)+cos ^2 13^o −(1/2)(2cos ^2 13^o −1)  = (3/4)+(1/2) = (5/4)

Answered by Dwaipayan Shikari last updated on 03/Jul/20

(cos47°+cos73°)^2 −(1/2)(cos120°+cos26°)+(1/2)  =cos^2 13°−(1/2)(2cos^2 13°−1)+(1/4)+(1/2)  =1+(1/4)=1.25